Fairest of all - Mlynowski, Sarah (New York : Scholastic Press, 2012)
After moving to a new house, ten-year-old Abby and her younger brother Jonah discover an antique mirror that transports them into the Snow White fairy tale.
400
Accelerated Reader AR
Keywords: Fairy tales -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction